Macroprudential policies and financial stability - Hughes Hallett, Andrew ([Caribbean Centre for Money and Finance] [St. Augustine]TT, 2009)
Assesses to what extent the central bank or the government should respond to developments that can cause financial instability, such as housing or asset bubbles, overextended budgetary policies, or excessive public and household debt.